PENGARUH PENYULUHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DENGAN PENGGUNAAN MEDIA VIDEO TERHADAP PENGETAHUAN TENTANG DETEKSI DINI KANKER PAYUDARA PADA SISWI MA PONDOK PESANTREN AN NI’MAH BATAM - Lubis, Leli Suryani; Susanti, Susanti (Universitas Batam, 2021)
Breast cancer is the number one leading killer of women. Breast cancer is a disease that occurs due to overgrowth or uncontrolled development of tissue cells in the breast. Early detection of breast cancer can be done by the breast self-examination which can reduce mortality rate by 25-30%. The purpose of the research was to find out the effect of breast self-examination counselling on knowledge about early detection of breast cancer by using video at An Ni’mah Boarding School Batam in 2020. It used pre-experiment design by one group pre-test post-test. Population was 80 people. Sampling technique was total sampling. Media used was video. Data collected by using questionnaire. Data analysed by normality test and used T-test. Based on the research result, knowledge about early detection of breast cancer before being given counseling and after being given counseling from the bivariate test results using T-test obtained p-value 0.000 (p < 0.05), so Ha was accepted. There was an increasing of mean value before giving the counselling (48.19) and after giving the counselling mean value was 83.21. It can be concluded there was a significant difference between knowledge scores before and after being given breast self-examination counselling by using video. It can be concluded that there was an effect of breast self-examination Counselling on knowledge about early detection of breast cancer by using video in female students.